The potential of online learning in modern conditions and its use at different levels of education - Danchikov, Evgeniy Aleksandrovich; Prodanova, Natalia Alekseevna; Kovalenko, Yulia Nikolaevna; Bondarenko, Tatiana Grigorievna (Linguistics and Culture Review, 2021)
The purpose of the work is to explore the potential of online learning in modern conditions and to assess the possibilities of its use at different stages of the educational process. The reason for the mass appeal to this form of education is that the entire education system from primary to higher level underwent a transformation during the period of isolation associated with the spread of COVID-19. Practice has shown that in the current conditions, the existing resources of educational institutions can effectively transform formal education into online education with the help of virtual classes and other key online tools. Today, taking into account the unstable epidemiological situation in the world, online training continues to be relevant for various educational organizations and is used today along with the traditional form of training. For this reason, the study of the potential of this form of education will not lose its relevance for a long time. The use of online learning technologies places high demands on teachers.